Fear of failure among perfectionist students - Alethea Rachel Xi Ern Lee; Zahari Ishak; Mansor Abu Talib; Yi Ming Ho; Kususanto Ditto Prihadi; Abdul Aziz (International Journal of Evaluation and Research in Education (IJERE), 2024)
Fear of failure (FOF) has been reported as a construct that hinders individuals from achieving higher, working harder, and even moving from one stage of development to another. Studies indicated that university students with traits perfectionism tend to develop FOF, which prevented them for achieving better accomplishment in their academic life. In order to obtain further knowledge to curb FOF among this population, this study investigates which one of the three dimensions of perfectionism (self-oriented, other-oriented, socially prescribed) is the main predictor of FOF. 351 participants from the target population of 4,000 undergraduate students from UCSI University, Kuala Lumpur, Malaysia were recruited via convenience sampling to provide us with their data through a Google Form. Perfectionism dimensions were measured by the multidimensional perfectionism scale and fear of failure by the performance failure appraisal inventory. The collected data was analyzed via simple and multiple regression by multiple regression technique, and the findings showed that self-oriented and other-oriented perfectionism did not significantly predict the fear of failure. However, socially prescribed perfectionism was the only significant predictor of the fear of failure among the perfectionism model, therefore indicating that it was the most significantly predictor as well. In conclusion, students are more likely to be afraid to fail when they believe that there is a social standard of perfection that they have to follow.